Effect Of Annealing Time On The Properties Of Interstacked Magnesium-Doped Cu₂O/Cuo Thin Films - Mohd Yusri, Fatin Nur Afiqah; Razalli, N. N.; Mohammad Zain, M. Z.; Mahyiddin, M.; Aiman, A.F.; Jaafar, H.; Mohamad, F.; Khoo, P. L.; Izaki, M. (International Journal of Integrated Engineering, 2025)
Cuprous oxide (Cu₂O) is an attractive candidate for cost-effective and sustainable solar cells due to its direct bandgap and natural p-type conductivity. We report on the investigation of the effect of annealing time on the morphological, optical, structural and electrical properties of interstacked Mg:Cu₂O/CuO thin films. The thin films were synthesized using the electrodeposition method of Cu₂O layers on indium tin oxide (ITO) substrate followed by annealing at 300°C for different durations (60, 120, 180, and 240 minutes). As a result, we found that by increasing annealing time up to 180 minutes, the formation of CuO thin film increases, surpassing the Cu₂O as revealed by X-ray diffraction (XRD) analysis. The band gaps remain constant at 2.5 eV, irrespective of annealing time. Carrier concentration increased upon the annealing time, reaching a value of 2.255 x 10²¹ (/cm³), which demonstrates the complementary effects of magnesium (Mg) doping and annealing time.